Who is the Populist Irish Voter? - Reidy, Theresa; Suiter, Jane (SSISI, 2017)
Across the EU, the Great Recession begot economic and political crisis heralding a renewed march towards populism and party system fragmentation. Much commentary about Ireland remarked on the absence of a populist surge of the type seen in many other bailout states (Clifford, 2016; Pappas, 2015). But is this characterization of the Irish experience accurate? The imposition of austerity policies and the protracted recovery propelled long standing critics of the Irish economic model centre stage and in common with many other states, party system fragmentation advanced with the long dominant centrist parties suffering severe losses at general elections (Marsh, Farrell and McElroy, 2017; Kriesi et al., 2016). New and more radical political forces did emerge and general elections in 2011 and 2016 were among the most volatile in Western Europe since 1945. The traditional parties of government experienced a sharp contraction in their vote shares but they retained their hold on power and the parties which have been labelled populist, remain some distance from entering into government. The focus of research on populism in Ireland has been on the supply side to date, looking at parties and campaigns (O’Malley and Fitzgibbon, 2015; Suiter, 2017) and this paper seeks to further the debate by investigating voter attitudes. Using data from the 2016 Irish National Election Study, the paper will demonstrate that many voters hold views which are populist. Irish voters are most likely to hold anti-elite and anti system populist attitudes, sometimes labelled left-wing populism in the literature and a smaller group hold strong outgroup and national identity views, often times called nativism or right-wing populism. Anti-elite populists are most likely to support Sinn Féin, Fianna Fáil and Independents while outgroup and national identity populists lean strongly towards Fianna Fáil and Sinn Féin.
read before the Society, 20 April 2017; Symposium 2016-2017: Globalisation, Inequality and the Rise of Populism
Keywords: 314.15